Foucault and Brown: Disciplinary Intersections - Niki Kasumi Clements (Foucault Studies, 2022)
From the 1981 “Sexuality and Solitude” to the 1982 “Le combat de la chasteté” to the 1984 History of Sexuality, Volume 2, Michel Foucault’s published works have long recognized the influence of the historian of late antiquity, Peter Brown. With the 2018 publication of Foucault’s draft of Les Aveux de la chair (Confessions of the Flesh) bearing no mention of Brown, the depth of this influence requires further elaboration. Despite Brown not appearing in the “Index of Modern Authors,” Confessions of the Flesh reflects Foucault’s debt to Brown for his readings of Augustine of Hippo and his conceptualizations of sexuality and subjectivity.